2018
DOI: 10.1108/arj-01-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of international financial reporting standards on fund performance

Abstract: This paper examines the effect of IFRS on the performance of UK investment closed-end trust funds with domestic equity focus using Carhart's Four-Factor model. Design/methodology/approach The paper is based on the Efficient Market Hypothesis, which argues that all available information is already included in the price of assets and therefore, investors cannot beat the market or generate abnormal returns. Findings The results show that on average UK investment trusts do not generate abnormal returns, nor is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…But, in a later section of our paper, we also estimate abnormal returns using the Fama & French 3-factor model (Eq. ( 7)) which has been used in some papers in the area (e.g., Rubanov and Nnadi 2018;Su et al 2019;Li et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…But, in a later section of our paper, we also estimate abnormal returns using the Fama & French 3-factor model (Eq. ( 7)) which has been used in some papers in the area (e.g., Rubanov and Nnadi 2018;Su et al 2019;Li et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Different studies have suggested that the business cycle has nonlinear properties and economic variables display asymmetries throughout economic booms and busts [11][12][13]. The nonlinear models are interchangeable LSTM and RNN, whereas the LR and ARIMA are linear and sublinear models.…”
Section: Literature Workmentioning
confidence: 99%